2014
DOI: 10.4236/jacen.2014.32007
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring MVOC Profiles over Time from Isolates of Aspergillus flavus Using SPME GC-MS

Abstract: Fungi produce a variety of microbial volatile organic compounds (MVOCs) during primary and secondary metabolism. The fungus, Aspergillus flavus, is a human, animal and plant pathogen which produces aflatoxin, one of the most carcinogenic substances known. In this study, MVOCs were analyzed using solid phase microextraction (SPME) combined with GCMS from two genetically different A. flavus strains, an aflatoxigenic strain, NRRL 3357, and a non-aflatoxigenic strain, NRRL 21882. A PDMS/CAR SPME fiber was used ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 28 publications
2
12
1
Order By: Relevance
“…To the best of our knowledge, none of the reported molecules have previously been measured in the headspace of A. fumigatus cultures, likely because the hypoxia-associated volatile metabolome of this organism has never been measured. Five of the six molecules (excluding benzonitrile) have, however, been measured in the headspace of either Aspergillus flavus or Aspergillus niger cultures [35, 36]. …”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, none of the reported molecules have previously been measured in the headspace of A. fumigatus cultures, likely because the hypoxia-associated volatile metabolome of this organism has never been measured. Five of the six molecules (excluding benzonitrile) have, however, been measured in the headspace of either Aspergillus flavus or Aspergillus niger cultures [35, 36]. …”
Section: Resultsmentioning
confidence: 99%
“…Using peak area %, the RSD%'s of CAR/PDMS, DVB/CAR/PDMS and DVB/PDMS are 56.7%, 52.1% and 39.5%, respectively. Previous studies show that RSD%'s determined using analytical standards calculated by peak area were 18.4%, 14.9% and 13.1%, for CAR/PDMS, DVB/CAR/PDMS and DVB/PDMS, respectively [32]. Several volatile metabolites show large fluctuations in concentration under identical experimental condition; this is due in part to uninduced biological variation [48].…”
Section: Evaluation Of Spme Fiber On Metabolic Profilingmentioning
confidence: 99%
“…For SPME fiber evaluation, the extraction efficiencies of three commercially available SPME fibers coated with carboxen/polydimethylsiloxane (CAR/PDMS), divinylbenzene/polydimethylsiloxane (DVB/PDMS) and carboxen/divinylbenzene /PDMS were compared. A single A. flavus isolate was selected for this study in an attempt to reduce variations due to phenotype differences associated with different isolates [32]. For the growth parameters' effect study, the A. flavus isolate was grown under varied conditions using different temperatures and numbers of spores inoculated and on different substrates to evaluate the influence of these factors on MVOCs' production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we have identified 57 compounds already known to be emitted by fungi (Table 1). In particular, we have identified 13 compounds known to be associated with the fungal presence (a in Table 1) and/or the genus Aspergillus (b in Table 1), and more precisely, 44 compounds known in the literature to be involved with the presence of A. flavus strains (c in Table 1) [10,23,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. In addition, 20 compounds (not counting the 6 unidentified compounds) were identified for the first time to be emitted by A. flavus.…”
Section: Mvocsmentioning
confidence: 99%